The role of the interferon/JAK-STAT axis in driving islet HLA-I hyperexpression in type 1 diabetes - Russell, Mark A.; Richardson, Sarah J.; Morgan, Noel G. (Frontiers in Endocrinology, 2023)
The hyperexpression of human leukocyte antigen class I (HLA-I) molecules on pancreatic beta-cells is widely accepted as a hallmark feature of type 1 diabetes pathogenesis. This response is important clinically since it may increase the visibility of beta-cells to autoreactive CD8+ T-cells, thereby accelerating disease progression. In this review, key factors which drive HLA-I hyperexpression will be explored, and their clinical significance examined. It is established that the presence of residual beta-cells is essential for HLA-I hyperexpression by islet cells at all stages of the disease. We suggest that the most likely drivers of this process are interferons released from beta-cells (type I or III interferon; possibly in response to viral infection) or those elaborated from influent, autoreactive immune cells (type II interferon). In both cases, Janus Kinase/Signal Transducer and Activator of Transcription (JAK/STAT) pathways will be activated to induce the downstream expression of interferon stimulated genes. A variety of models have highlighted that HLA-I expression is enhanced in beta-cells in response to interferons, and that STAT1, STAT2 and interferon regulatory factor 9 (IRF9) play key roles in mediating these effects (depending on the species of interferon involved). Importantly, STAT1 expression is elevated in the beta-cells of donors with recent-onset type I diabetes, and this correlates with HLA-I hyperexpression on an islet-by-islet basis. These responses can be replicated in vitro, and we consider that chronically elevated STAT1 may have a role in maintaining HLA-I hyperexpression. However, other data have highlighted that STAT2-IRF9 may also be critical to this process. Thus, a better understanding of how these factors regulate HLA-I under chronically stimulated conditions needs to be gathered. Finally, JAK inhibitors can target interferon signaling pathways to diminish HLA-I expression in mouse models. It seems probable that these agents may also be effective in patients; diminishing HLA-I hyperexpression on islets, reducing the visibility of beta-cells to the immune system and ultimately slowing disease progression. The first clinical trials of selective JAK inhibitors are underway, and the outcomes should have important implications for type 1 diabetes clinical management.